ECOLOGICAL OCCURANCE OF HIMALAYAN POPLAR (POPULUS CILIATA WALLICH EX ROYLE) AND ITS NURSERY EVALUATION UNDER TEMPERATE CONDITIONS OF KASHMIR - T. H. MASOODI,; AHMAD, HILLAL; S. A. GANGOO,; P. A. SOFI,; M. A. BHAT,; M. A. ISLAM, (The Bioscan, 2014)
The present study was conducted to elucidate the ecological occurrence of an endangered indigenous Himalayan poplar “Populus ciliata” in the temperate coniferous forests of Kashmir. In all, the species was found growing in three ecological blocks of occurrence viz. forests as climax species, evolved riparian phase with willows and colonization phase as pure stunted crop. The cuttings (25cm long and 1cm thick) collected from one year old branches were planted in nursery beds at a spacing of 1 × 1ft in the month of February. About 90% of cuttings sprouted and developed roots. The germplasm collected from these ecological blocks was screened for their growth pattern for two years under field conditions in the nursery. A significant phenotypic variation was observed and clones from all the three ecological blocks of occurrence varied in growth characteristics and biomass production potential. The seedlings raised from clones obtained from natural climax forests exhibited maximum plant height (87.2 cm), collar diameter (11.21 mm), number of branches (3.50), dry weight (114.15 gm), number of leaves (22.10) and leaf area (1021.30 cm2). However, significant (pd” 0.05) differences were recorded almost in all parameters between site and year and also in its interactions, except in case of Root Shoot ratio. Owing to this superior growth, the half sib clones collected from the mixed climax forests with climax phase were multiplied and out planted for conservation and further evaluation.